Switching long acting antipsychotic medications to aripiprazole long acting once-a-month: expert consensus by a panel of Italian and Spanish psychiatrists. Issue 4 (2nd April 2016) - Fagiolini, Andrea; Alfonsi, Emilia; Amodeo, Giovanni; Cenci, Mario; Di Lella, Michele; Farinella, Francesco; Ferraiuolo, Fabrizio; Fraguas, David; Loparco, Natale; Gutierrez-Rojas, Luis; Mignone, Maria Laura; Pataracchia, Giuseppe; et al.
ABSTRACT: Introduction : Aripiprazole long acting once-monthly (AOM) is a long acting atypical antipsychotic with proven efficacy in schizophrenia and with a pharmacological and a side effect profile that is different from other antipsychotics. These and other characteristics make AOM a possible alternative in patients requiring a change in long acting antipsychotic treatment due to issues such as lack of efficacy or persistent side effects. Both clinical and pharmacological factors should be considered when switching antipsychotics, and specific guidelines for long acting antipsychotic switching that address all these factors are needed. Areas covered : A panel of Italian and Spanish experts in psychiatry met to discuss the strategies for the switch to AOM in patients with schizophrenia. Real life clinical experiences were shared and the clinical strategies to improve the likelihood of success were discussed. Expert Opinion : Due to its specific pharmacological and tolerability profile, AOM represents a suitable alternative for patients with schizophrenia requiring a switch to a new LAI treatment because of lack of efficacy or persistent side effects from another LAI. Possible strategies for the switch to AOM are presented in this expert consensus paper in an attempt to provide guidance throughout the entire switching process